2019
DOI: 10.1016/j.ajic.2019.05.032
|View full text |Cite
|
Sign up to set email alerts
|

Effects of environmental disinfection on the isolation of vancomycin-resistant Enterococcus after a hospital-associated outbreak of Middle East respiratory syndrome

Abstract: Environmental disinfection with sodium hypochlorite and hydrogen peroxide vapor was performed after a hospital-associated outbreak of Middle East respiratory syndrome. Although only 11% of total beds were disinfected, the isolation and vancomycin-resistance rates of Enterococcus spp significantly decreased for 2 months, whereas other multidrug-resistant organisms did not.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…High efficiency particulate air (HEPA) filters were installed in the breathing circuits, both on the inspiratory and expiratory limbs of the ventilators and at the patient's site that connected to endotracheal tube. After operations with MERS-exposed patients, 30 minutes of room ventilation was followed by surface disinfection with diluted chlorine bleach (500 ppm) 18,19 . Cleaners wore standard PPE while disinfecting surfaces.…”
Section: Equipment Preparation and Disinfectionmentioning
confidence: 99%
“…High efficiency particulate air (HEPA) filters were installed in the breathing circuits, both on the inspiratory and expiratory limbs of the ventilators and at the patient's site that connected to endotracheal tube. After operations with MERS-exposed patients, 30 minutes of room ventilation was followed by surface disinfection with diluted chlorine bleach (500 ppm) 18,19 . Cleaners wore standard PPE while disinfecting surfaces.…”
Section: Equipment Preparation and Disinfectionmentioning
confidence: 99%
“…Theoretical models and scoring systems exist but are mostly difficult to implement in practice [29]. units, operating theatres and clean rooms, respectively, considered high-risk areas.…”
Section: Key Components I) Risk Assessmentmentioning
confidence: 99%
“…In addition, Dancer et al were able to show that introducing an additional environmental services staff member for enhanced cleaning of hand-touch sites in surgical wards with endemic Another prospective study by Rutala et al found a 35% reduction in colonization and/or infection with epidemiologically important pathogens when the contamination was reduced by 94% due to enhanced terminal cleaning [26]. Further studies confirmed the positive impact of enhanced environmental cleaning and disinfection protocols on infection and/or colonization rates of MRSA [27], VRE [17,28,29] and Clostridioides difficile [16,[30][31][32][33][34].…”
Section: Introductionmentioning
confidence: 98%
“…The middle East respiratory syndrome coronavirus (MERS-CoV) is a zoonotic beta coronavirus which can infect various kinds of animals such as humans, camels, and bats. [118][119][120][121][122][123] It belongs to the Beta-coronavirus genus, of the coronavirus family. 124,125 It was first discovered in September 2012 as the cause of death in a patients who had died of severe pneumonia in June 2012 in Jeddah, Saudi Arabia, 126,127 and 1,348 cases of MERS-CoV infection confirmed globally, with at least 479 related deaths until June 23, 2015.…”
Section: The Middle East Respiratory Syndrome Coronavirus (Mers-cov)mentioning
confidence: 99%